Repeated thyroid function evaluations in the dog: a retrospective study of 8,309 dogs - Oberbauer, Anita M.; Belanger, Janelle M.; Petroff, Brian K.; Brown, Diane E.; Wolfe, Christopher R.; Famula, Thomas R. (Frontiers in Veterinary Science, 2025)
Hypothyroidism in dogs is a common diagnosis with some breeds being more prone to the condition. Autoimmune thyroiditis has an inherited component. Breeders wish to reduce the incidence by any means possible. Currently, the only opportunity lies in phenotypic testing of thyroid functionality. This retrospective study evaluated thyroid hormone and thyroglobulin autoantibodies (TgAA) analyses in dogs assessed multiple times to determine if the outcome changed over time. Data were extracted from the Orthopedic Foundation for Animals (OFA) database for 8,309 dogs which had been evaluated two or more times and the initial classification was compared to a final classification. More than 90% of dogs evaluated as normal for thyroid function remained normal in follow-up assessments. The greatest change was seen for dogs initially evaluated as equivocal; this was followed by a compensative autoimmune thyroiditis diagnosis being revised to normal, though 50% of the latter evaluation remained classified as compensative autoimmune thyroiditis. This suggests the presence of low levels of autoantibodies may be transient and that a dog presenting with autoantibodies should be reevaluated to confirm the development of autoimmune thyroiditis.